PENGARUH BEBAN KERJA, KOMPETENSI SERTA KOMPENSASI TERHADAP PRESTASI KERJA KARYAWAN HOTEL EXCELTON PALEMBANG - Liliana Liliana; Muhni Pramuji (P3M STIE Mulia Darma Pratama, 2021)
This study aims to determine the Effect of Workload, Competence and Compensation on Employee Performance at Excelton Hotel Palembang. The data used in this study are primary and secondary data, with data collection techniques carried out through questionnaire distribution to 68 employees of the Excelton Hotel Palembang. The analysis technique used is multiple linear analysis techniques that are processed using the help of the computer program Statistics Product and Service Soulution (SPSS 22). From the results of the study there is a positive and significant influence of Workload, Competence and Compensation on Employee Performance at the Excelton Hotel Palembang, which is indicated by the Regression model = 38.016 + 0.850X1 + 0.427X2 + 0.657X3 + e. Simultaneous correlation between the Work Load independent variable (X1), Competency independent variable (X2), Compensation independent variable (X3) to Work Performance dependent variable (Y) equals 0.724 means that there is a strong and positive directional relationship. Partial correlation of Workload (X1) to Work Achievement (Y) equals 0.562 means that there is a fairly strong and positive relationship in the same direction, partial correlation of Competence (X2) to Work Achievement (Y) equals 0.581 means that there is a strong enough relationship and positive direction, partial correlation Compensation (X3) to Job Performance (Y) equals 0.613 means that there is a strong and positive directional relationship. This can be seen from the large coefficient of determination which is quite strong at 50.8% so there are still 49.8% of variables that cannot be examined. From the results of data conducted by researchers known Workload (X1), Competence (X2), Compensation (X3) significantly influence Work Performance (Y) of Excelton Hotel Palembang Employees with a calculated F value of 23,480 and a significant probability of 0.00 <0, 05. Workload (X1) has a significant effect on Work Performance (Y) with a calculated T value of 3.496 and a significant probability of 0.001 <0.05. Competence (X2) has a significant effect on Job Performance (Y) with a calculated T value of 2.033 and a significant probability of 0.04 <0.05. Compensation (X3) has a significant effect on Job Performance (Y) with a calculated T value of 2.776 and a significant probability of 0.007 <0.05.